Anti-cancer immune effect of human colorectal cancer neoantigen peptide based on MHC class I molecular affinity screening - Zhang, Siyu; Huang, Changxin; Li, Yongqiang; Li, Zhaoyang; Zhu, Ying; Yang, Lili; Hu, Haokun; Sun, Quan; Liu, Mengmeng; Cao, Songqiang (Frontiers in Immunology, 2024)
Background Tumor antigen peptide vaccines have shown remarkable efficacy, safety, and reliability in recent studies. However, the screening process for immunopotent antigenic peptides is cumbersome, limiting their widespread application. Identifying neoantigen peptides that can effectively trigger an immune response is crucial for personalized cancer treatment. Methods Whole exome sequencing was performed on patient-derived colon cancer cells to predict 9-amino-acid (9aa) neoantigen peptides. In vitro simulation of endogenous antigen presentation by antigen-presenting cells (dendritic cells) to CD8+ T cells was conducted, aiming to activate the CD8+ immune response to the predicted antigens. The immunological effects of each neoantigen were assessed using flow cytometry and ELISpot assays, while the relationship between neoantigen immunogenicity and MHC molecular affinity was examined. Results 1. Next-generation sequencing (NGS) predicted 9-amino acid (9aa) neoantigen peptides for subsequent immunological analysis. 2. Higher mDC Levels in Experimental Group: CD11c+CD83+ mature dendritic cells (mDCs) were 96.6% in the experimental group, compared to 0.051% in the control group. CD80 fluorescence intensity was also significantly higher in the experimental group, confirming a greater mDC presence. 3. Neoantigen Peptides Promote CD4+, CD8+ T, and NK Cell Proliferation: After 14 days, flow cytometry showed higher percentages of CD4+ T (37.41% vs 7.8%), CD8+ T (16.67% vs 4.63%), and NK cells (33.09% vs 7.81%) in the experimental group, indicating that the neoantigen peptides induced proliferation of CD4+, CD8+ T cells, and NK cells. 4. The results, analyzed using two-way ANOVA, showed that the standardized T-value for HLA molecular affinity variation in the 1-4 range (Group B) was significantly higher than for ≤1 (Group A, p < 0.0001) and >4 (Group C, p < 0.05). Regarding HLA-allele genotypes, HLA-Type 1 had a significantly higher standardized T-value than HLA-Type 2 (p < 0.05) and HLA-Type 3 (p < 0.0001). HLA-Type 1 was identified as the allele associated with the highest T-value. Conclusion 1. The most immunogenic neoantigens typically exhibit an MHC molecular affinity variation between 1 and 4, indicating that stronger immunogenicity correlates with higher MHC molecular affinity variation. 2. Each patient's HLA molecules were classified into Types 1, 2, and 3, with Type 1 showing the highest binding capacity for neoantigens. Our findings indicate that the most immunogenic neoantigens were associated with HLA Type 1. 3. Neoantigen peptides were shown to activate the proliferation of both CD8+ T-cells and induce proliferation of CD4+ T-cells and NK cells. 4. Variation in MHC molecular affinity and HLA neoantigen genotype are anticipated to serve as valuable variables for screening highly immunogenic neoantigens, facilitating more efficient preparation of effective polypeptide tumor vaccines.